Regulation and safety measures for nanotechnology-based agri-products - Kumari, Ritika; Suman, Kalpana; Karmakar, Swagata; Mishra, Vandana; Lakra, Sameer Gunjan; Saurav, Gunjan Kumar; Mahto, Binod Kumar (Frontiers in Genome Editing, 2023)
There is a wide range of application for nanotechnology in agriculture, including fertilizers, aquaculture, irrigation, water filtration, animal feed, animal vaccines, food processing, and packaging. In recent decades, nanotechnology emerged as a prospective and promising approach for the advancement of Agri-sector such as pest/disease prevention, fertilizers, agrochemicals, biofertilizers, bio-stimulants, post-harvest storage, pheromones-, and nutrient-delivery, and genetic manipulation in plants for crop improvement by using nanomaterial as a carrier system. Exponential increase in global population has enhanced food demand, so to fulfil the demand markets already included nano-based product likewise nano-encapsulated nutrients/agrochemicals, antimicrobial and packaging of food. For the approval of nano-based product, applicants for a marketing approval must show that such novel items can be used safely without endangering the consumer and environment. Several nations throughout the world have been actively looking at whether their regulatory frameworks are suitable for handling nanotechnologies. As a result, many techniques to regulate nano-based products in agriculture, feed, and food have been used. Here, we have contextualized different regulatory measures of several countries for nano-based products in agriculture, from feed to food, including guidance and legislation for safety assessment worldwide.